Artificial Intelligence and Islamic Law: Ethical Implications and Fiqh Fatwas in the Digital Age - Malik, Ridwan; Malik, Abdul; Mustika, Mega (Journal of Family Law and Islamic Court, 2024)
The advancement of Artificial Intelligence (AI) in the digital era has significantly influenced various fields, including health, education, and the legal system. However, alongside its potential benefits, AI also presents complex ethical and legal challenges, particularly within the framework of Islamic law, which is grounded in the Qur'an, Hadith, and fiqh traditions. This study examines how core principles of Islamic law—maslahah mursalah (public good), qiyas (analogy), and dhaman (accountability)—can address these challenges. Additionally, it evaluates the role of fatwas in offering adaptive and relevant legal guidance for modern technological developments. Using a document analysis approach, the research reveals that Islamic law possesses the flexibility to tackle issues such as algorithmic bias, data privacy, and accountability in autonomous decision-making. The principle of maslahah supports the ethical use of AI for the greater public good, while qiyas facilitates the legal adaptation of emerging technologies through analogy with established precedents. Meanwhile, dhaman underscores the necessity of human responsibility in the deployment of AI. However, existing fatwas are often too general and lack detailed guidance on addressing the specific complexities of AI, highlighting the need for a holistic approach that integrates classical Islamic principles with contemporary technological contexts. This research contributes by proposing a more comprehensive ethical and legal framework that aligns AI development and application with Islamic values. Recommendations include producing more detailed fatwas and conducting empirical research involving scholars, policymakers, and technology developers to ensure AI's responsible and beneficial utilization in the digital age.